Yesus dalam Perspektif Multikultural: Studi Perbandingan Kristologi di Berbagai Konteks - Lisdayanti Tinambunan; Jhon Rafael; Rike Yulianingsih; Sarmauli Sarmauli (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Christology studies have various aspects, including historical, theological, social and cultural aspects in understanding the person and work of Jesus Christ. Christology does not only focus on Church doctrine, but also studies the meaning of Jesus in a broader context, including relationships with other religions, social struggles, and liberation. This research is a qualitative research using a literature study method. Research as an effort to examine comprehensively through Christology in various contexts that penetrate social, cultural and religious interactions, as well as through traditional dogmatic understanding.